2004
DOI: 10.1161/01.res.0000150593.30324.42
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Microscopy of Cells and Tissue

Abstract: Abstract-Two-photon excitation fluorescence imaging provides thin optical sections from deep within thick, scattering specimens by way of restricting fluorophore excitation (and thus emission) to the focal plane of the microscope. Spatial confinement of two-photon excitation gives rise to several advantages over single-photon confocal microscopy. First, penetration depth of the excitation beam is increased. Second, because out-of-focus fluorescence is never generated, no pinhole is necessary in the detection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(224 citation statements)
references
References 80 publications
(131 reference statements)
4
218
0
2
Order By: Relevance
“…A high sensitivity of Di-4-ANEPPS to changes in V m was confirmed in the present study, whereas Fura-2 has a dissociation constant to free Ca 2+ of 224nM in the presence of 1mM Mg 2+ [16], which is close to diastolic intracellular [Ca 2+ ] in cardiomyocytes (150-300nM) [1]. This makes Di-4-ANEPPS and Fura-2/AM amenable to prolonged experiments in cardiac preparations, which coupled with the minimally invasive nature of 2P excitation [10][11][12] precedes other available techniques.…”
Section: Strengthssupporting
confidence: 73%
See 1 more Smart Citation
“…A high sensitivity of Di-4-ANEPPS to changes in V m was confirmed in the present study, whereas Fura-2 has a dissociation constant to free Ca 2+ of 224nM in the presence of 1mM Mg 2+ [16], which is close to diastolic intracellular [Ca 2+ ] in cardiomyocytes (150-300nM) [1]. This makes Di-4-ANEPPS and Fura-2/AM amenable to prolonged experiments in cardiac preparations, which coupled with the minimally invasive nature of 2P excitation [10][11][12] precedes other available techniques.…”
Section: Strengthssupporting
confidence: 73%
“…As such, laser power may be increased as focal depth is increased in order to maintain signal, as out-of-focus signal does not interfere [10,11]. Thus, deep imaging of multi-cellular preparations with high spatial resolution optical sectioning including along the Z-axis is achieved without the need for a F o r P e e r R e v i e w 4 detector pinhole (which is required in 1P excitation confocal microscopy to eliminate out-of-focus fluorescence emission), which further increases the fluorescence collection efficiency [11,12]. This, coupled with the availability of voltage-and Ca 2+ -sensitive dyes that fluoresce after 2P excitation [13,14] allowed us to develop protocols for high-resolution deep imaging of AP and intracellular Ca 2+ characteristics of in situ cardiomyocytes in intact, perfused whole hearts.…”
Section: Introductionmentioning
confidence: 99%
“…When the fluorescence techniques are applied on the level of tissues or whole organisms, strong limitations appear due to low penetration of light in these media because of high absorbance and light-scattering. Presently in this case the 'labeling' technology has definite advantages, since it allows free selection of fluorescence reporters including the dyes excited in the near-IR range 800-1,000 nm (the wavelength range of maximal transparency of living tissues) (Ntziachristos et al 2004;Smith et al 2011b), the fluorescent nanoparticles exhibiting upconversion phenomenon (Nagarajan and Zhang 2011) or applying two-photon excitation (Rubart 2004). In the case of deeply located cells and dense tissues the probing with radioactive or MRI contrast agents (Blankenberg and Norfray 2011) or smart nanoparticles that combine MRI and fluorescence responses (van Tilborg et al 2006) was suggested.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The first 2-photon excitation of electronic states was found for blue fluorescence emission with CaF 2 :Eu 2+ crystals based on the availability of lasers in 1961 (Kaiser & Garrett, 1961). To date, tunable mode-locked Ti:sapphire lasers operating at high repetition rate (typically 80-90 MHz) and a ultrashort pulse duration (less than 200 fs) are typically used as near infrared (NIR) sources in multiphoton excitation imaging (König & Riemann, 2003;Zipfel et al, 2003b;Rubart, 2004;Wang et al, 2005a). The required transient high irradiance can be obtained by tightly focusing ultrashort laser pulses within a sub-femtolitre focal volume provided by a special objective with high numerical aperture.…”
Section: Introductionmentioning
confidence: 99%